Social Aquaculture Model for Sustainable Rural Development - Adrian Gheorghe Zugravu; Ionica Soare (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2015)
The paper follows two main objectives: to understand aquaculture farmers’ perception and image of social services and to identify communication levers in order to improve the perceived image of social farming. Orientations in terms of communication are product-focused and aim at enhancing the reputation of social farming consequently with impact on rural development. This paper conducted a questionnaire survey of Romanian aquaculture farmers’ perception toward social agricultural. The empirical study indicated that farmers shown different awareness to social farming.